COMPARISON OF MALE AND FEMALE VICTIMS OF INTIMATE PARTNER HOMICIDE AND BIDIRECTIONALITY- AN ANALYSIS OF THE NATIONAL VIOLENT DEATH REPORTING SYSTEM - Velopulos, Catherine G; Carmichael, Heather; Zakrison, Tanya L; Crandall, Marie (The journal of trauma and acute care surgery, 2019)
Intimate partner violence (IPV) is a public health crisis, affecting at least 1:4 women and 1:9 men. A recent multi-center trial on universal screening in trauma patients showed similar rates of positive screens between men and women. Few studies have explored the bidirectional violence in opposite sex or same sex relationships. Our goal was to estimate prevalence and risk factors for the most severe manifestation of IPV: intimate partner homicide (IPH). This is a 2003-2015 retrospective review of the National Violent Death Reporting System (NVDRS), a CDC database of surveillance data. Deaths were coded IPV if the primary relationship between the suspect and victim fell into the categories of "current partner" or "ex-partner." Bivariable and multivariable analysis examined differences between groups for factors and circumstances. 6,131 persons in opposite-sex relationships and 181 in same-sex relationships were murdered due to IPV. Women and Black men were disproportionately affected, and alcohol and preceding arguments were a factor in a higher proportion of male victims. Abuse preceded homicide in many women with almost half of male suspects attempting or committing suicide at the time of IPH. Women were more likely than men to use a stabbing instrument, although firearms were still the most common means for each group. In 46.5% of homicides of women, the male suspect attempted suicide (p <0.001). Bidirectionality was highest in male victims of female perpetrators, and in same-sex pairings regardless of sex of the victim. Homicide due to IPV is a significant public health crisis for both men and women, with women and Black men at particular risk. Firearms are the most commonly used weapon for homicide in both genders, and mental illness is not a common risk factor. A staggering proportion of these homicides involve suicide of the suspect, suggesting that each potential incident has two victims to target for prevention and intervention. Interventional programs to prevent such bidirectional mortality are urgently needed. III STUDY TYPE: Retrospective Secondary Data Analysis.